Alterations in expression of Cat‐315 epitope of perineuronal nets during normal ageing, and its modulation by an open‐channel NMDA receptor blocker, memantine. Issue 9 (26th March 2017) - Yamada, Jun; Ohgomori, Tomohiro; Jinno, Shozo
Abstract: The perineuronal net (PNN), a specialized aggregate of the extracellular matrix, is involved in neuroprotection against oxidative stress, which is now recognized as a major contributor to age‐related decline in brain functions. In this study, we investigated the age‐related molecular changes of PNNs using monoclonal antibody Cat‐315, which recognizes human natural killer‐1 (HNK‐1) glycan on aggrecan‐based PNNs. Western blot analysis showed that the expression levels of Cat‐315 epitope in the hippocampus were higher in middle‐aged (MA, 12‐month‐old) mice than in young adult (YA, 2‐month‐old) mice. Although there were no differences in the expression levels of Cat‐315 epitope between old age (OA, 20‐month‐old) and MA mice, Cat‐315 immunoreactivity was also detected in astrocytes of OA mice. To focus on Cat‐315 epitope in PNNs, we used YA and MA mice in the following experiments. Optical disector analysis showed that there were no differences in the numbers of Cat‐315‐positive (Cat‐315 + ) PNNs between YA and MA mice. Fluorescence intensity analysis indicated that Cat‐315 immunoreactivity in PNNs increased with age in the dorsal hippocampus, which is mainly involved in cognitive functions. Administration of an open‐channel blocker of NMDA receptor, memantine, reduced the expression levels of Cat‐315 epitope in the hippocampus. Furthermore, the numbers of glutamatergic and GABAergic terminals colocalized with Cat‐315 epitope around parvalbumin‐positive neurons were decreased by memantine. These findings provide novel insight into the involvement of PNNs in normal brain ageing, and suggest that memantine may counteract the age‐related alterations in expression levels of Cat‐315 epitope via regulation of its subcellular localization. Abstract : Monoclonal antibody Cat‐315 recognizes HNK‐1 glycan in aggrecan‐based PNNs. Expression of Cat‐315 epitope in PNNs is increased in the mouse hippocampus during normal aging. Administration of an open‐channel blocker of NMDA receptor, memantine, counteracts the age‐related changes in expression levels and subcellular localization of Cat‐315 epitope.